2009
DOI: 10.3390/ijerph6010361
|View full text |Cite
|
Sign up to set email alerts
|

Engagement and Action for Health: The Contribution of Leaders’ Collaborative Skills to Partnership Success

Abstract: A multi-site evaluation (survey) of five Kellogg-funded Community Partnerships (CPs) in South Africa was undertaken to explore the relationship between leadership skills and a range of 30 operational, functional and organisational factors deemed critical to successful CPs. The CPs were collaborative academic-health service-community efforts aimed at health professions education reforms. The level of agreement to eleven dichotomous ('Yes/No') leadership skills items was used to compute two measures of members' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It is surprising that research within the field of sport and physical activity partnerships has not received the same attention as in other policy areas for example, health promotion, where partnership working has been consistently endorsed and scrutinised (Butterfoss et al 1996;El Ansari et al 2009;Kegler et al 1998). County Sport Partnerships have provided the main focus of research in the present context given their relevance to the wider narrative on partnership approaches within policy making.…”
Section: Research Into Partnerships For Sport and Physical Activitymentioning
confidence: 99%
“…It is surprising that research within the field of sport and physical activity partnerships has not received the same attention as in other policy areas for example, health promotion, where partnership working has been consistently endorsed and scrutinised (Butterfoss et al 1996;El Ansari et al 2009;Kegler et al 1998). County Sport Partnerships have provided the main focus of research in the present context given their relevance to the wider narrative on partnership approaches within policy making.…”
Section: Research Into Partnerships For Sport and Physical Activitymentioning
confidence: 99%
“…Factors described as facilitating effective health networking include effective leadership [ 11 ], bridging nodes between organisations ([ 12 ], p.30), and brokerage where behaviours are closely managed, people from diverse backgrounds are synthesized together, effective communication is engendered and operating rules developed ([ 8 ], p.15). Homophily, or the tendency of individuals to associate and bond with similar nodes, has been shown to be important in facilitating networks [ 5 , 12 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In health promotion, a common pitfall is that training is usually provided for the intervention (smoking cessation); but the vehicle of the intervention (partnership) itself is not viewed as a bone fide intervention that also merits experience, expertise and training. Partnership working is a science and art [ 2 ]. Hence in assessing whether the partnership was successful or not, collectively, these characteristics suggested that it is not merely the ‘obligatory’ nature of the collaboration between municipalities that is at hand, but a myriad of other factors need to be simultaneously considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, although current smoking rates among adults in Denmark are around the same as the Organization for Economic Co-operation and Development countries’ average, they are still higher than in other Scandinavian countries [ 1 ]. In many countries, tobacco control and smoking cessation efforts have employed multi-stakeholder partnership arrangements for smoking cessation, as the recent decades witnessed partnerships being increasingly initiated and utilized to address a wide range of public health challenges [ 2 , 3 ]. Hence, collaborative projects that address tobacco consumption have been instigated between countries or researchers [ 4 ], sometimes employing community-primary care-academic partnership models [ 5 ].…”
Section: Introductionmentioning
confidence: 99%